Aktivitas Antiinflamasi Gel Ekstrak Rumput Mutiara (Ordelandia corymbosa L.) Pada Tikus (Rattus norvegicus L.) Yang Diinduksikan Karagenan - Ince Agus Nurcholis; Yusriadi Yusriadi; Evi Sulastri (Biology Department, Mathematics and natural science, Tadulako University, 2018)
Pearl grass is usually used in traditional medicine for the treatment of inflammation. This research aims to determine the anti inflammatory activity of pearl grass extract gel in rats induced by carrageenan and to evaluate the physical stability of its formulation during the storage of 14 days. The gel physical stability tests consist of organoleptic test, homogeneity, pH viscosity and dispersive power. Anti inflammatory activity test were divided into 5 treatment groups. Group 1 was given a gel without active ingredients as a negative control, group 2 were given diclofenac sodium gel as a positive control and group 3, 4 and 5 were given pearl grass extract gel at concentration of 5%, 10% and 15%. The measurements of inflammation volume were performed for 6 hours with intervals of 60 minutes. The results showed that all formulas have good physical stability during storage for homogeneity testing but having instability on pH, viscosity and dispersive power. The activity test showed all formulas have anti-inflammation against carrageenan induced rat. Gel with a concentration of 10% (F2) which more effective to reduce inflammation than the other formulas was selected as the most optimum formula. Key words : Gel, extract gel, pearl grass, Ordelandia corymbosa L., antiinflammatory